ISLAMIC RELIGIOUS EDUCATION TEACHERS' STRATEGY IN MASTERING ARABIC VOCABULARY IN STUDENTS THROUGH PICTURE CARD MEDIA AT SMP MUHAMMADIYAH 07 MEDAN - Friska Indriani; Hasrian Rudi Setiawan (RADJA PUBLIKA, 2025)
Arabic is one of the fields of study taught at the Junior High School level or equivalent. This study discusses the improvement of students' vocabulary mastery through picture card media in Arabic subjects at SMP Muhammadiyah 07 Medan. This study uses a qualitative method with a descriptive approach. The results of this study indicate an increase in students' vocabulary mastery through picture card media in Arabic subjects at SMP Muhammadiyah 07 Medan. The results obtained in this study, namely the application of the vocabulary card method accompanied by pictures in Arabic language learning, have proven to be very efficient in facilitating and improving students' memorization in learning Arabic vocabulary.